Biochemical Analysis in Pesticide Exposed Freshwater Fish from Muda Area, Kedah - Tajul Hassan, Mohd Zahari (2006)
The widespread and indiscriminate use of pesticides has led to the contamination of the aquatic environment, particularly on aquatic organisms such as the freshwater fish. Pollution of aquatic environment by pesticides results in biochemical, behavioral, morphological, histopathological and molecular changes in fish. This study was carried out to compare between the fish bred at the Pusat Penetasan Ikan, Universiti Putra Malaysia labeled as the control and the fish collected from Kawasan Muda, Kedah labeled as exposed, to the biochemical changes and the relation to fish quality. The water sample analysis taken from paddy field in the Muda, Kedah area showed the pesticide content known as alpha-endosulfan, beta-endosulfan, delta-BHC, lindane, dieldrin, endrin, 4,4-DDD, 4,4-DDT dan endrin aldehyde. The water sample analysis taken from the Pusat Penetasan Ikan, UPM did not indicate the presence of pestisid. The fish species selected in this study were ikan keli (Clarias batrachus), haruan (Channa striata), puyu (Anabas testudineus) dan sepat siam (Trichogaster pectoralis). All the exposed fish species showed a difference in the total protein, lactate and glycogen contents in the muscle compared to the control fish. For the nucleotide contents estimation, the adenosine-5-triphosphate (ATP) content for all the exposed fishes was found to be decreased between 12-50% and the inosine-5- monophosphate (IMP) was increased compared to the control fish. For the fish quality, the K values for all exposed fishes were found to be increased compared to the control fish. The increment of the K values of 3-4% indicated that the fishes were of still good quality and is fit for human consumption. Keli which was exposed to 10.8 μg/L endosulfan for 96 hours was used as positive control. From the study, the total protein and glycogen content in the muscle was found to be decreased. For the nucleotide contents, the ATP content was found to be decreased and the IMP content was decreased compared to control. For the K value, the exposed fish were found to be decreased in the first 12 hours and increased at 7-14% after 24 hours of exposure to endosulfan.